A bibliometric analysis of blue carbon (1993–2023): evolution of research hot topics and trends - Wang, Shanshan; Yan, Dandan; Wang, Chenhao; Wu, Linlin; Huang, Yiming (Frontiers in Marine Science, 2024)
Blue carbon refers to the carbon fixed in marine ecosystems such as mangroves, salt marshes, and seagrass beds. Considered a treasure house for capturing and storing carbon dioxide, it can alleviate environmental issues linked to climate change and positively influence the environments where people live. Thus, to clarify the hotspots and development trends of blue carbon research, bibliometric analysis incorporating ScientoPy and VOSviewer software were used to quantitatively analyze 4,604 blue carbon publications from Web of Science and Scopus databases between 1993 and 2023. The results indicate a rapidly growing number of published studies on blue carbon, with blue carbon research being multifaceted and gradually becoming an interdisciplinary and international topic. This study on blue carbon, which is based on keyword clustering analysis, comprises three stages. The analysis of the strength of the cooperative connections between scholars in various countries who have published work on blue carbon. found that the cooperation networks of developed countries are strong and those of developing countries are relatively weak. Quantitative trend analysis reveals a growing focus on the restoration and conservation of blue carbon ecosystems, with remote sensing being the predominant technology used in the blue carbon research field in recent years. In blue carbon research, increasing carbon sequestration capacity, climate change mitigation, and carbon sequestration in macroalgae remain potential hotspots for research and development.